Tratamiento especializado del abuso o dependencia del alcohol - Villalbí Hereter, Joan Ramon; Bosque Prous, Marina; Brugal Puig, María Teresa; Suelves Joanxich, Josep Maria; Espelt Hernández, Albert (Revista española de salud pública, 2014)
Background: The National Plan for Drugs in Spain (PNSD) fostered the prevention and treatment of illegal drug use disorders, and now also covers alcohol use disorders. The goal of this paper is to estimate the number of persons in specialized treatment because of alcohol in public services. Methods: Review of the key documents of the PNSD, the drug information system of Catalonia, and the Barcelona drug information system. For Catalonia and Barcelona data from 1991 to 2010 are presented. Results: In recent years, there has been more information available for Spain as a whole, of varying validity and comprehensiveness. In Catalonia, the number of reported admissions to treatment for alcohol use disorders has risen: alcohol causes yearly over 40% of all admissions in the drug addiction treatment network; mean age is 44 years, and 23% are women. In Barcelona, admissions to treatment due to alcohol are more than 2.000 each year, relative frequency is 217 by 100.000 residents over 15 years for men and 67 for women. Conclusions: Available data shows that for alcohol, the drug information system needs further development in Spain, solving methodological issues. Available data for Catalonia suggests that the network of drug treatment centres has improved treatment for alcohol use disorders along with that of illegal drugs. This information is relevant, as there is almost no population based treatment data. This information should be completed for other Regional Administrations. Fundamentos: El Plan Nacional sobre Drogas (PNSD) impulsó la prevención y el tratamiento de los trastornos por uso de drogas ilegales, y ahora abarca los trastornos por uso de alcohol. El objetivo de este trabajo es realizar una estimación de las personas en tratamiento especializado por alcohol en la red pública. Métodos: Se revisan documentos del PNSD, del sistema de información sobre drogodependencias de Cataluña y del de Barcelona. Para Cataluña y Barcelona se presentan datos de 1991 a 2010. Resultados: Para el conjunto de España hay información disponible desde hace pocos años, con exhaustividad y validez variable. En Catalunya, el número de admisiones a tratamiento por alcohol notificadas se incrementó: el alcohol causa anualmente más del 40% del total de admisiones a tratamiento en la red de drogodependencias; la edad media es de 44 años y el 23% son mujeres. En Barcelona las admisiones a tratamiento por alcohol superan las 2.000 al año, suponiendo 217 por 100.000 habitantes mayores de 15 años varones y 67 en mujeres. Conclusiones: Los datos disponibles sugieren que por lo que respecta al alcohol el sistema de información sobre drogas ha de desarrollarse más en España, resolviendo problemas metodológicos. Los datos disponibles para Cataluña sugieren que la red de atención a drogas ha permitido abordar la necesidad asistencial por dependencia al alcohol conjuntamente con la de drogas ilegales. Esta información es relevante, pues apenas existen datos de tratamiento referidos a la población.